Enhanced Antitumor Effect in Liver Cancer by Amino Acid Depletion-Induced Oxidative Stress - Okuda, Keiichiro; Umemura, Atsushi; Kataoka, Seita; Yano, Kota; Takahashi, Aya; Okishio, Shinya; Taketani, Hiroyoshi; Seko, Yuya; Nishikawa, Taichiro; Yamaguchi, Kanji; Moriguchi, Michihisa; Nakagawa, Hayato; et al. (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. HCC cells consume large amounts of glutamine to survive, but can adapt to glutamine depletion in the presence of an exogenous asparaginase. L-asparaginase (ASNase) converts glutamine and asparagine to glutamate and aspartate, respectively, and has been used to treat leukemia. Here we examined the effects of ASNase treatment on HCC cells and explored the potential impact of combining ASNase with the tyrosine kinase inhibitor lenvatinib (Len) for HCC treatment. Cell viability and death of HCC cell lines treated with either Len or ASNase alone or with Len and ASNase combined were determined. We assessed mRNA and protein expression levels of glutamine synthetase (GS) and asparagine synthetase (ASNS) by real-time quantitative PCR and immunoblotting. The antitumor effect of the combination therapy relative to Len or ASNase monotherapy was also evaluated in a xenograft tumor mouse model. ASNase treatment inhibited growth of SNU387 and SNU398 HCC cells, which have low GS and high ASNS expression levels, respectively, but did not clearly inhibit growth of the other cell lines. Len plus ASNase combination therapy synergistically inhibited proliferation and induced oxidative stress leading to cell death of some HCC cells lines. However, cell death of Huh7 cells, which express ASCT2, an important glutamine transporter for cancer cells, was not affected by the combination treatment. In a xenograft model, Len combined with ASNase significantly attenuated tumor development relative to mice treated with Len or ASNase alone. ASNase-mediated targeting of two amino acids, glutamine and asparagine, which are indispensable for HCC survival, induces oxidative stress and can be a novel cancer treatment option that exerts a synergistic effect when used in combination with Len.